DEVELOPMENT OF THEMATIC STUDENTS WORK SHEET (LKPD) BASED ON 21th CENTURY COMPETENCY THEME 7 SUBTHEME 1 LEARNING 1 CLASS V SD LEDUG STATE - Ainun Fitri Nur Khasanah; Sony Irianto; Arifin Muslim (Universitas Negeri Medan, 2020)
Abstract:This study aims to produce a Student Worksheet (LKPD) based on 21st century student competence theme 7 subtheme 1 learning 1 in class V SDN Ledug. This research is a development study with development procedures according to Thiagarajan, Semmel and Semmel which include: defining, design, developing, disseminating. The results of this study indicate that: (1) Development of Thematic LKPD based on 21st Century Student Competencies Theme 7 Subtheme 1 Learning 1 in grade V of primary schools can be used as teaching material that can be used to supplement thematic teaching materials in primary schools, (2) Assessment validation of experts / experts on the results of the development of LKPD obtained an average of 4.1, which means valid, (3) Teacher's assessment of Thematic LKPD based on 21st Century Student Competencies Theme 7 Subthemes 1 Learning 1 in class V gained an average of 4.5 which included in the category of